Per un’estetica dell’erranza Marrani, nicodemiti e filosofi in transito nel mondo globalizzato del XVI e XVII Secolo - Dalla Vigna , Pierre (Scenari, 2024)
The Jews of Spain, in 1492, were forced to convert to Christianity or leave the country. But even those who agreed to convert, the Marranos, were always persecuted by the Inquisition and often burned at the stake. The Marranos also therefore sought refuge elsewhere.This exodus took them to Portugal, Italy, the Arab countries and the Ottoman Empire, and then, starting from Holland, also to Asia and the Americas. In this way, the Marranos were among the most important actors in trade and relations on a global scale. Furthermore, forced to continuously change religion, status, nation and ideologies, the Marranos are at the basis of the formation of the new subjectivities of the modern age, represented by artists and writers such as Cervantes and Velázquez, by theologians such as Servetus, by philosophers such as Spinoza, by mystics like Teresa of Avila.